2020
DOI: 10.1016/j.cytox.2020.100035
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab for severe COVID-19 related illness – A community academic medical center experience

Abstract: Highlights COVID-19 can cause a hyperinflammatory state akin to cytokine release syndrome (CRS). Our report shows the efficacy and safety of using anti-IL-6/IL-6-R therapy in 31 patients. Treatment at the onset of severe CRS may be the ideal window for intervention. Long term effects of these agents are currently lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, all antibodies prevent the binding of IL-6 to IL-6R and inhibit classic and trans -signaling equally well ( 30 ). Consistently, the IL-6R antibodies tocilizumab and sarilumab demonstrated beneficial effects on survival rates in severe COVID-19 cases in preclinical and clinical studies ( 9 11 , 31 ). However, IL-6 is required to control viral infection ( 32 ); hence, global blockade of IL-6 signaling, e.g., through tocilizumab, is associated with an increased risk of airway infections ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 71%
“…However, all antibodies prevent the binding of IL-6 to IL-6R and inhibit classic and trans -signaling equally well ( 30 ). Consistently, the IL-6R antibodies tocilizumab and sarilumab demonstrated beneficial effects on survival rates in severe COVID-19 cases in preclinical and clinical studies ( 9 11 , 31 ). However, IL-6 is required to control viral infection ( 32 ); hence, global blockade of IL-6 signaling, e.g., through tocilizumab, is associated with an increased risk of airway infections ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 71%
“…Tocilizumab (TCZ) is a well-established IL-6 receptor monoclonal antibody that inhibits both the classical and trans-signaling axis widely used for the PLOS PATHOGENS treatment of rheumatoid arthritis. Several clinical outcomes suggested that an early use of tocilizumab is beneficial for survival, reduction of hospitalization stay, and duration of oxygen support in COVID-19 patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous antibiotics were given to patients with elevated procalcitonin, positive sputum or blood culture and/or elevated CRP in whom concurrent bacterial infection was suspected. Tocilizumab was administered to patients who had the following parameters: ferritin ≥600 ng/mL, CRP ≥80 mg/L 32 and IL-6 >37.65 pg/ml. 33 We recorded 10 (16.4%) deaths during the study period, all of which occurred among the RC group.…”
Section: Resultsmentioning
confidence: 99%